190k views
2 votes
Given the function h(x) = -x2 - 6x +11,determine the average rate of change of thefunction over the interval -4 < x < -1.

Given the function h(x) = -x2 - 6x +11,determine the average rate of change of thefunction-example-1
User Dvir
by
5.3k points

1 Answer

6 votes

The average rate of change of a function f(x) over the interval


a\le x\le b

is given by the expression


\text{ Average rate of change }=(f(b)-f(a))/(b-a)

So, in this case, you have


\begin{gathered} a=-4 \\ b=-1 \\ h(x)=-x^2-6x+11 \\ h\mleft(a\mright)=h\mleft(-4\mright)=-(-4)^2-6(-4)+11=-16+24+11=19 \\ \text{ Then} \\ h(-4)=19 \\ h(b)=h(-1)=-(-1)^2-6(-1)+11=-1+6+11=16 \\ \text{ Then} \\ h(-1)=16 \end{gathered}

Finally, you have


\begin{gathered} \text{ Average rate of change }=(h(b)-h(a))/(b-a) \\ \text{ Average rate of change }=(h(-1)-h(-4))/(-1-(-4)) \\ \text{ Average rate of change }=(16-19)/(-1+4) \\ \text{ Average rate of change }=(-3)/(3) \\ \text{ Average rate of change }=-1 \end{gathered}

Therefore, the average rate of change of the function over the given interval is -1.

User VoxPelli
by
6.3k points